THE DYNAMICS OF IMPLEMENTING SHARIA ACCOUNTING STANDARD IN SHARIA FINANCIAL INSTITUTION - Qimyatussa‘adah, .; Sayeed, Raihand Ramadhani Abdul (International Journal of Islamic Banking and Finance Research, 2024)
This study investigates the dynamics of Sharia Accounting Standards (SAS) implementation in Indonesian sharia-compliant financial institutions. The adoption of SAS is essential for ensuring consistency and transparency in financial reporting within the Islamic finance sector. However, the process faces several challenges, including differences in practitioners' understanding and expertise of Sharia accounting principles. To explore these dynamics, a systematic literature review was conducted, focusing on publications related to SAS and its application in Islamic finance. The results reveal that multiple factors influence the adoption of SAS. Technical issues, such as varying levels of comprehension and expertise among practitioners, hinder effective implementation. Furthermore, governance issues, stemming from different models of Shariah compliance across countries and varying stages of growth in the Islamic finance sector, add complexity. Additional challenges include the alignment with the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) standards, conflicts between multiple accounting frameworks, and the lack of a unified accounting structure. The study also highlights the disparities in SAS application across Islamic financial institutions. Some institutions exhibit high levels of compliance and effective integration, while others struggle with the implementation. Factors such as inadequate human resources, differences in interpreting SAS, and the need for adjustments to accounting systems further complicate the process. The findings suggest that while the implementation of SAS faces significant challenges, regulatory support, enhanced education and training, and increased collaboration among sharia financial institutions can improve the effectiveness of Sharia-compliant financial reporting in Indonesia.JEL Classification Codes: M4, M41, P43.